Z- and E-selective Horner–Wadsworth–Emmons reactions. Issue 13 (3rd July 2017) - Molnár, Katalin; Takács, László; Kádár, Mihály; Faigl, Ferenc; Kardos, Zsuzsanna
ABSTRACT: In the present work, we determined and evaluated the stereochemical outcome of the Horner–Wadsworth–Emmons (HWE) reaction of 2-oxoalkylphosphonates with different ester functions (bis(2, 2, 2-trifluoroethyl), 2, 2, 2-trifluoroethyl methyl, dimethyl) and side chains (aliphatic, aromatic) with three different aldehydes (benzaldehyde, THP- and PPB-protected Corey aldehydes) under two reaction conditions. The " trans " protocol is generally used in the E -selective HWE reactions, while " cis " protocol promotes the Z -selectivity. GRAPHICAL ABSTRACT: